School–family relationships, school satisfaction and the academic achievement of young people. Issue 2 (15th March 2017) - Hampden-Thompson, Gillian; Galindo, Claudia
Abstract: Families' perceptions of, and interactions with, schools and teachers can play an essential role in young people's educational outcomes. According to Bronfenbrenner's ecological systems theory, young people grow within multiple nested systems of influence interacting with each other. Thus, their development is affected by persons, processes, and institutions at all levels, from their family, to the school they attend, to society. This study examined the role of school–family relationships, parents' school satisfaction, and their associations with educational achievement. Drawing upon data from over 10, 000 students from the Longitudinal Study of Young People in England, the results of the multivariate analysis indicated that while positive school–family relationships are a predictor of achievement, this association is mediated by the degree of parents' satisfaction with their child's school. We concluded that the combination of strong school–family relationships and high levels of school satisfaction provides a boost for young people's academic success. Therefore, school policies and practices that enhance relationships with families and improve levels of parent satisfaction can result in rewards for all young people including those from poor backgrounds.